Immobilized enzyme-driven value enhancement of lignocellulosic-based agricultural byproducts: Application in aroma synthesis. (15th February 2021) - Costa-Silva, T.A.; Carvalho, A.K.F.; Souza, C.R.F.; De Castro, H.F.; Bachmann, L.; Said, S.; Oliveira, W.P.
Abstract: We have combined the advantages of immobilization and spouted bed drying to enhance lipase activity and stability for further use of this enzyme in esterification. Through covalent binding, Cercospora kikuchii lipase was immobilized onto agricultural byproducts activated with glutaraldehyde, sodium periodate, or epichlorohydrin. The immobilized derivatives showed high lipase activity retention (from 83.8 to 116.9%) and low residual moisture (average of 3.96%) and water activity (average of 0.19). The kinetic parameters KM and Vmax of the free lipase were 0.212 mM and 160.3 μmol/min/mg, respectively; lipase immobilized onto the support activated with 1.5% glutaraldehyde had lower KM (0.121 mM) and higher Vmax (275.4 μmol/min/mg). Lipase immobilized onto rice husk retained 60.3% of its initial enzyme activity after five reuse cycles, and its residual activity was high 88.7% after storage at 5 °C for six months. This immobilized derivative system was used to catalyze butyl butyrate synthesis. Under the best conditions for butyl butyrate production (temperature of 50 °C and enzyme concentration of 0.5 g), the esterification yields reached 95.0% and afforded a butyl butyrate concentration of 15.2 g/L. The enzyme stability, high activity retention after reuse cycles, and ability to catalyze butyl butyrate synthesis from butyric acid strongly indicate that the innovative one-step immobilization protocol reported herein is feasible for lipase immobilization onto the surface of eco-friendly supports. Graphical abstract: Image 1 Highlights: Agricultural byproducts as a "green" support for enzyme immobilization. Spouted bed dryer to lipase immobilization by a single step. The immobilized derivatives showed high enzyme activity retention and stability. Spouted bed drying can be successfully used for thermally sensitive biomolecules. Immobilized lipase provided an excellent esterification yield as high as 95.0%.